2018
DOI: 10.3389/fpsyg.2018.00692
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Wisdom Structure: Validation of the Spanish New Short Three-Dimensional Wisdom Scale (3D-WS) and Its Explanatory Power on Psychological Health-Related Variables

Abstract: Introduction: Personal wisdom has demonstrated important implications for the health of individuals. The aim of the present study was to validate a Spanish version of the Three-Dimensional Wisdom Scale (3D-WS), exploring the structure of a possible general factor, and assessing its explanatory power on psychological health-related variables.Methods: A cross-sectional study design was used, with a total sample of 624 Spanish participants recruited on the Internet and randomly split into two halves. The followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…The results confirmed our initial hypothesis, with high scores on the WADES being associated with the ability to accept and be aware of emotions, the ability to implement emotion regulation strategies, control impulses and develop goals in emotional situations. The relation between the WADES and the Difficulties in Emotion Regulation Scale (DERS) of the present study is in line with those found when measuring the cognitive and affective components of the three-dimensional wisdom scale (García-Campayo et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…The results confirmed our initial hypothesis, with high scores on the WADES being associated with the ability to accept and be aware of emotions, the ability to implement emotion regulation strategies, control impulses and develop goals in emotional situations. The relation between the WADES and the Difficulties in Emotion Regulation Scale (DERS) of the present study is in line with those found when measuring the cognitive and affective components of the three-dimensional wisdom scale (García-Campayo et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…The typically measured item is “If I see people in need, I try to help them one way or another” ( Ardelt, 2003 ). Thus, the higher scores of women on this dimension indicate that in the process of interpersonal communication, women are more sensitive to the emotions of others than men and have more positive behavior and emotional reaction, and fewer indifferent attitudes and negative reactions ( García-Campayo et al, 2018 ). This gender difference was true both for individuals in early adulthood (18–29 years old; Beaumont, 2011 ) and the elderly (52–87 years old; Ardelt, 2009 ).…”
Section: Gender and Wisdom Levelmentioning
confidence: 99%
“…Three-Dimensional Wisdom Scale (3D-WS) [38]: Scale that seeks to measure 3 dimensions in relation to wisdom, based on the Ardelt scale in 2003 and validated and translated into Spanish by García-Campayo [38]. The scale is made up of three subdimensions with a total of 39 items.…”
Section: Instrumentsmentioning
confidence: 99%
“…Although, the measurement of wisdom through questionnaires, although it may be simplistic because it is thought that it is affected by biases such as social desirability [47], has advantages by offering a simple and fast means to approach the base empirically and that it allows to know antecedents, starting situation and consequences. It should be noted that there are different investigations that have translated the 3D-WS scale into different languages, but they are very recent studies [38,48,49].…”
Section: Preprints (Wwwpreprintsorg) | Not Peer-reviewed | Posted: 21 December 2021mentioning
confidence: 99%